119. Safety and Reactogenicity of an Investigational Respiratory Syncytial Virus (RSV) Prefusion F Protein Vaccine for Adults ≥ 60 Years of Age (RSVPreF3 OA): an Interim Analysis at 6 Months after Vaccination. (15th December 2022) - Schwarz, Tino F; Hwang, Shinn-Jang; Ylisastigui, Pedro P; Liu, Chiu-Shong; Takazawa, Kenji; Yono, Makoto; Ervin, John E; Andrews, Charles; Fogarty, Charles; Eckermann, Tamara; Vicco, Miguel; Lievens, Marc; et al.
Abstract: Background: RSV causes respiratory infections that can lead to serious respiratory complications in older adults (OA). Presently, there is no approved vaccine to prevent RSV infections. RSVPreF3 OA is an investigational vaccine containing 120 µg RSVPreF3 and the AS01E adjuvant. Here we show safety results up to month (M) 6 post-vaccination with RSVPreF3 OA. Methods: This phase 3 multi-country ongoing study (NCT04732871) enrolled adults ≥ 60 years of age over a period of 3 years. Participants were randomized (3:1:1) to receive RSVPreF3 OA with different vaccination schedules. All participants received a dose of RSVPreF3 OA on day 1. Solicited and unsolicited adverse events (AEs) were evaluated within 4 and 30 days post-vaccination. All serious AEs (SAEs) and potential immune mediated diseases (pIMDs) were collected up to M6 post-vaccination. SAEs and pIMDs related to vaccination, and fatal AEs are collected up to study end but reported here up to M6. Results: Overall, 1653 participants received a dose of RSVPreF3 OA and 1618 completed the M6 follow-up. The mean age was 70.0 (±6.6) years and 54.6% were women. The most frequently reported solicited injection site reaction within 4 days post-vaccination was pain (996 participants; 60.5%, 95% confidence interval [CI]: 58.1–62.9). Twenty-two participants (1.3%, 95% CI: 0.8–2.0) reported grade 3 pain (Figure). The most reported solicited systemic reactions were myalgia (551 participants; 33.5%, 95% CI: 31.2–35.8) and fatigue (517 participants; 31.4%, 95% CI: 29.2–33.7). Twenty-five participants (1.5%) reported fever (no grade 3). Most solicited AEs were transient lasting ∼2 days and were of mild to moderate intensity. Overall, 212 (12.8%, 95% CI: 11.3–14.5) participants reported at least 1 unsolicited AE within 30 days post-vaccination. At least 1 SAE was reported by 65 participants (3.9%, 95% CI: 3.0–5.0). Seven participants (0.4%, 95% CI: 0.2–0.9) reported at least 1 pIMD. Of the SAEs and pIMDs reported, 1 event (Guillain-Barre syndrome) was considered by the investigator as related to vaccination. Fatal SAEs were reported for 6 participants; none related to vaccination. Conclusion: One dose of investigational RSVPreF3 OA vaccine was well tolerated and had an acceptable safety profile in adults ≥ 60 years of age. Funding: GlaxoSmithKline Biologicals SA. Disclosures: Tino F. Schwarz, Prof. Dr. MD, Biogen, Merck-Serono, Pfizer, Alexion, Bavarian Nordic, Janssen-Cilag, AstraZeneca, Biontech, MSD: Grants|GlaxoSmithKline Biologicals SA: Honoraria John E. Ervin, MD, The Alliance for Multispecialty Research – KCM: Contractual agreement for conduct of study protocol Charles Andrews, MD, GlaxoSmithKline Biologicals SA: Institutional grant|Merck and Boehringer Ingelheim: Consulting fees outside of the submitted work Miguel Vicco, PhD MD, GlaxoSmithKline Biologicals SA: Employee|GlaxoSmithKline Biologicals SA: Stocks/Bonds Marc Lievens, MSc, GlaxoSmithKline Biologicals SA: Employee|GlaxoSmithKline Biologicals SA: Stocks/Bonds Céline Maréchal, PhD, GlaxoSmithKline Biologicals SA: Employee|GlaxoSmithKline Biologicals SA: Stocks/Bonds Phoebe Nakanwagi, Master's in Biostatistics, GlaxoSmithKline Biologicals SA: Employee Veronica Hulstrøm, PhD MD, GlaxoSmithKline Biologicals SA: Employee.